INDIRECT COMPOSITE VENEERS AS A SOCIAL THERAPEUTIC SOLUTION. A CASE REPORT - Alice-Arina; Maria Alexandra Martu; Magda Ecaterina Antohe; Ionut Luchian; Ioana Martu; Ioana Sioustis; Gabriela Ifteni (Romanian Society of Oral Rehabilitation, 2019)
The modern dentistry area addresses high demands for dental restorations, harmoniously integrating into the homeostasis of the dental system. Modern contemporary aesthetic restorations are commonly associated with the latest CAD-CAM biomaterials and technologies, with prep- and no-prep techniques. Current practice often faces us with an important decision-maker, the socio-economic criterion, which limits the therapeutic options. In this context, the chosen therapeutic alternatives need to restore both aesthetics and functionality to optimal parameters in the financial terms which are accessible to the specific social segment. The article presents the case of a young woman that presented to the dental clinic for aesthetic reasons. The therapeutic option consisted in the restoration of the physiognomic function using composite veneers made by indirect method.